Pengembangan Aplikasi Dan Pelatihan Sistem Informasi TPQ Madinah Ma’arif 10 An-Nur Kota Malang - Wakhidah, Rokhimatul; Affandi, Luqman; Shoumi, Milyun Ni'ma; Kirana, Annisa Puspa; Hormansyah, Dhebys Suryani; Arief, Sofyan Noor (DIKEMAS (Jurnal Pengabdian Kepada Masyarakat), 2022)
Advances in information technology have a major impact on the use of technology in various fields, one of which is education. Information technology is used as a means to simplify the teaching and learning process to the management of educational institutions. Almost all educational institutions have utilized information technology, one of which is the application of an integrated information system to handle administrative affairs of educational institutions. TPQ Madinah Ma'arif 10 An-Nur is one of the TPQ that has implemented advances in information technology. This is reflected in the use of value input information systems and the printing of student report cards. Over time, this feature has not met the needs of the management in carrying out TPQ operational activities. TPQ institutions do not yet have a system that handles the presence of students. And there is no system that handles the recording of payments